Tackling inequalities in obesity: a protocol for a systematic review of the effectiveness of public health interventions at reducing socioeconomic inequalities in obesity among adults - Bambra, C.L.; Hillier, F.C.; Moore, H.J.; Cairns-Nagi, J.M.; Summerbell, C.D. (Systematic Reviews, 2013)
Background: Socioeconomic inequalities in obesity and associated risk factors for obesity are widening throughout developed countries worldwide. Tackling obesity is high on the public health agenda both in the United Kingdom and internationally. However, what works in terms of interventions that are able to reduce inequalities in obesity is lacking. Methods/Design: The review will examine public health interventions at the individual, community and societal level that might reduce inequalities in obesity among adults aged 18 years and over, in any setting and in any country. The following electronic databases will be searched: MEDLINE, EMBASE, CINAHL, PsycINFO, Social Science Citation Index, ASSIA, IBSS, Sociological Abstracts, and the NHS Economic Evaluation Database. Database searches will be supplemented with website and gray literature searches. No studies will be excluded based on language, country or publication date. Randomized and non-randomized controlled trials, prospective and retrospective cohort studies (with/without control groups) and prospective repeat cross-sectional studies (with/without control groups) that have a primary outcome that is a proxy for body fatness and have examined differential effects with regard to socioeconomic status (education, income, occupation, social class, deprivation, poverty) or where the intervention has been targeted specifically at disadvantaged groups or deprived areas will be included. Study inclusion, data extraction and quality appraisal will be conducted by two reviewers. Meta-analysis and narrative synthesis will be conducted. The main analysis will examine the effects of 1) individual, 2) community and 3) societal level public health interventions on socioeconomic inequalities in adult obesity. Interventions will be characterized by their level of action and their approach to tackling inequalities. Contextual information on how such public health interventions are organized, implemented and delivered will also be examined. Discussion: The review will provide evidence, and reveal any gaps in the evidence base, of public health strategies which reduce and prevent inequalities in the prevalence of obesity in adults and provide information on the organization, implementation and delivery of such interventions. Systematic review registration: PROSPERO registration number: CRD42013003612
EPrint Processing Status: Full text deposited in DRO
Keywords: Obesity; Socioeconomic inequalities; Public health; Adults.